Nutritional value of hora and mineral-enriched soil for cattle: Evaluation of mineral composition and physicochemical properties in southwestern Ethiopia - Ashenafi Miresa; Taye Tolemariam; Belay Duguma; Ellen S. Dierenfeld; Geert P. J. Janssens; Abebe Nigussie; Feyissa Begna (PLoS ONE, 2026)
Natural mineral water (“ hora ”) and mineral-enriched surrounding soils are potential mineral supplements for cattle, yet comprehensive data on their physicochemical properties, mineral concentration and contribution to animal nutrition have been lacking. Thus, this study aimed to evaluate the mineral composition and physicochemical properties of hora , and the mineral-enriched surrounding soils in the study area. Hora and the soil samples were collected in triplicate from each district, processed, and analyzed for physicochemical properties and mineral concentrations. The physicochemical parameters (temperature, electrical conductivity, total dissolved solids, pH, dissolved oxygen, total hardness, total turbidity, sulfate, nitrate, ammonia, chloride), and mineral concentration (calcium, potassium, sodium, magnesium, phosphorus, sulfur, iron, zinc, copper, molybdenum, selenium, and manganese in hora and soil samples were examined. Results revealed significant variation (p < 0.05) in physicochemical properties and mineral concentrations of hora across the districts. While many physicochemical properties of hora were found within the critical range for cattle, elevated electrical conductivity (up to 2900 µ S/cm), total dissolved solids (up to 1700 mg/L), and ammonia (up to 1.14 mg/L), raise concerns for its suitability for cattle. Furthermore, soil concentrations of iron (31.4 g/kg), molybdenum (200 mg/kg), and manganese (921 mg/kg) exceeded maximum tolerable limits for cattle, indicating that unsupervised soil ingestion could negatively impact animal health. While these sources offer a promising natural mineral source, their high salinity and potentially toxic mineral levels in soil necessitate careful consideration for cattle nutrition. Therefore, further research is necessary to develop sustainable management strategies for hora and assess its long-term implications in animal nutrition and health.